1996
DOI: 10.1016/0014-5793(96)00974-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of residues in the putative 5th helical region of human interleukin‐6, important for activation of the IL‐6 signal transducer, gp130

Abstract: interaction (respectively termed a-and 13-sites) have been Abstract We have previously shown that L58 in the putative 5th helical region of human interleuidn-6 (IL-6) is important for identified and are dispersed throughout the putative tertiary activation of the IL-6 signal transducer gpl30 Ide Hon et al.structure (reviewed in [9]). The a-site is spatially separated (1995) FEBS Lett. 369, 187-1911. To further explore the from the I~-sites (l~l-~a), and is comprised of residues in the importance of individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Differences between the association of IL-27p28 and IL-6 with gp130 are due to two amino acid differences in the AB loop between IL-27p28 and IL-6 that increase the hydrophobicity of IL-27p28, and thus its affinity for gp130. Interestingly, it has previously been shown that mutations in the AB loop of human IL-6 contribute to the ability of mutant forms of IL-6 to antagonize wild-type IL-6 activity42. Furthermore, modeling studies incorporating fluorescence-correlation spectroscopy have proposed that a gp130 homodimer first binds one IL-6–IL-6Rα complex, and engages a second IL-6–IL-6Rα complex at higher ligand concentrations43.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the association of IL-27p28 and IL-6 with gp130 are due to two amino acid differences in the AB loop between IL-27p28 and IL-6 that increase the hydrophobicity of IL-27p28, and thus its affinity for gp130. Interestingly, it has previously been shown that mutations in the AB loop of human IL-6 contribute to the ability of mutant forms of IL-6 to antagonize wild-type IL-6 activity42. Furthermore, modeling studies incorporating fluorescence-correlation spectroscopy have proposed that a gp130 homodimer first binds one IL-6–IL-6Rα complex, and engages a second IL-6–IL-6Rα complex at higher ligand concentrations43.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with chimeras and mutant proteins defined three receptor binding sites, where site I (or site α; Brakenhoff et al, 1995Brakenhoff et al, , 1996 binds the gp80 and site II and III (Savino et al, 1994;Panoessa et al, 1995;Sporeno et al, 1996) bind to a gp130 chain (reviewed in Simpson et al, 1997). Studies with chimeras and mutant proteins defined three receptor binding sites, where site I (or site α; Brakenhoff et al, 1995Brakenhoff et al, , 1996 binds the gp80 and site II and III (Savino et al, 1994;Panoessa et al, 1995;Sporeno et al, 1996) bind to a gp130 chain (reviewed in Simpson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%